EFFECTIVENESS AND TOXICITY DIFFERENCES BETWEEN THE USE OF REGIMEN CHEMOTHERAPY BLEOMYCIN-VINCRISTINE-MITOMYCIN-CISPLATIN AND BLEOMYCIN- VINCRISTINE-MITOMYCIN-CARBOPLATIN FOR THREE CYCLES IN PATIENTS CERVICAL CANCER SQUAMOUS CELL STADIUM IIB-IIIB IN SANGLAH GENERAL HOSPITAL DENPASAR BALI Research Article - R, Noviyani; K, Suwiyoga; Ing, Budiana; K, Tunas; Pa, Indrayathi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: Medicines in the market need their security and their effectiveness monitored to ensure patient safety, which is called Clinical Testing Stage IV. Cytotoxic medicines especially those for cervical cancer chemotherapy, particularly need to be monitored. These medicines include two combinations: Bleomycin-vincristine-mitomycin-cisplatin (BOM-cisplatin) and bleomycin-vincristine-mitomycin-carboplatin (BOM-carboplatin). Both these combinations are commonly used for cervical cancer treatments in Sanglah General Hospital. Up till now, there has not been adequate data to differentiate between the two combinations. Therefore, we conducted the research to explore the relative effectiveness and toxicity of both combinations. The assessment of both combinations can be seen using parameter squamous cell carcinoma (SCC) and tumor-mass. Toxicity assessment of the chemotherapy can be seen by judging functions of the liver (serum glutamic oxaloacetic transaminase [SGOT], serum glutamic pyruvic transaminase [SGPT]), kidneys (blood urea nitrogen [BUN], creatinine), and blood (leukocytes, hemoglobin) of patients. Methods: The observational research with the cross-sectional method in Obstetrics and Gynecology Clinics in Sanglah General Hospital Denpasar Bali. Research on both combinations was carried out between 2013 and 2015. The samples were obtained before the 1 chemotherapy and after the 3 rd st chemotherapy, by using consecutive sampling method. Prodia Clinical Laboratory carried out examinations on levels of SCC, while tumor-mass and the other parameters were carried out by Clinical Pathology Laboratory Sanglah General Hospital. Data were analyzed with the paired t-test with 95% confidence interval, using SPSS 17.0 for Windows. Results: Samples used in this research was 12 patients who got combination BOM-cisplatin and 9 patients who got combination BOM-carboplatin. In the group of BOM-cisplatin, there is no difference of content of leukocytes, hemoglobin, creatinine, BUN, SGOT, SGPT, and SCC before the 1 st chemotherapy and after the 3 rd chemotherapy (*p>0.05). However, there are different levels of tumor mass before the 1 chemotherapy and after the 3 chemotherapy (*p<0.05). In the group of BOM-carboplatin, there are no differences in the levels of Creatinine, BUN, SGPT, SGOT, tumor mass, and SCC (*p>0.05). However, there are different levels of leukocytes and hemoglobin (*p<0.05). rd Conclusion: The use of combination BOM-cisplatin can be said to be effective by the change of patients' tumor-mass after undergoing chemotherapy. The combination BOM-carboplatin is not effective because there were no changes in patients' tumor-mass and patients' levels of antigen SCC, and has toxic effects on patients' blood after undergoing chemotherapy. Keywords: Effectiveness, Toxicity, Bleomycin-vincristine-mitomycin-cisplatin, Bleomycin-vincristine-mitomycin-carboplatin, Cervical cancer. st